Income distribution dynamics and pro-poor growth in the world from 1970 to 2003 - Hajo Holzmann; Sebastian Vollmer; Julian Weisbrod (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
We estimate and analyze the global income distribution from national log-normal income distributions for the years 1970 to 2003, as well as the income distribution of seven regional subsamples. From these distributions we obtain measures for global and regional inequality and poverty, and find decreasing global poverty and inequality during the time period. By decomposing inequality into within and between country inequality using Theils' measure of inequality, we observe declining inequality between countries whereas overall inequality within countries increased. Furthermore, we calculate growth incidence curves for five year periods between 1970 and 2003, as well as a growth incidence curve for the entire period and corresponding rates of pro-poor growth. In the global income distribution, the 8.5th to 63.5th global income percentiles experienced above average percentile growth rates, while the remaining very lowest quantiles experienced also the lowest percentile growth rates. Using the regional decomposition we find that while in 1970 more than half of the worlds extreme poor and poor people lived in East Asia, it is Sub-Saharan Africa where nowadays two thirds of the extreme poor and half of the worlds poor live.
Keywords: I32; I31; O47; F01; 330; Einkommensverteilung; Armut; Soziale Ungleichheit; Entwicklungskonvergenz; Wirtschaftswachstum; Welt